Genomic and transcriptomic landscape of carcinogenesis in patients with gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS) - Chihiro Matsumoto; Kazuki K. Takahashi; Masaaki Iwatsuki; Noriko Yasuda-Yoshihara; Atsushi Niida; Kohei Yamashita; Takeshi Morinaga; Kojiro Eto; Shiro Iwagami; Satoshi Ida; Hiromu Yano; Yoshihiro Komohara; et al. (Proceedings of the National Academy of Sciences, 2025)
Gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS) is an autosomal dominant syndrome characterized by polyposis localized in the gastric body and fundus with a strong tendency for adenocarcinoma. The genetic mutations that accumulate during the progression from normal mucosa through polyp to carcinoma in GAPPS remain unclear. We investigated the evolutionary process from normal mucosa to polyp and carcinoma in GAPPS. Through comprehensive mutational and transcriptome analyses, we aimed to provide insights into the biology of this disease. Whole-exome sequencing and RNA sequencing were performed on carcinoma, polyp, and normal mucosa samples from multiple sites from seven patients with GAPPS (n = 54 samples). We comprehensively investigated genomic alterations (including copy number alterations and somatic mutations), clonal architecture, and transcriptome dynamics during carcinogenesis. Genomic evolutionary analysis showed that in GAPPS, somatic mutations of APC occur in carcinoma and polyp while mutations of KRAS additionally occur in carcinoma. We also found the co-occurrence of APC and KRAS mutations in carcinoma recurrently both across cases and within subclones of the same case. The co-occurrence of APC/KRAS mutations may contribute to the carcinogenesis of GAPPS. Our study provides detailed information on the genomic and transcriptomic landscape in GAPPS carcinogenesis, conferring valuable insights into its underlying mechanisms.